2007
DOI: 10.1002/jtr.599
|View full text |Cite
|
Sign up to set email alerts
|

Swimming with captive dolphins: current debates and post‐experience dissonance

Abstract: Dolphins have widespread contemporary appeal and anthropomorphic social representations of dolphins have fuelled a growing desire in tourist populations to seek interaction with them. This paper is concerned with the staged performance of swim‐with‐dolphin interaction programmes in aquaria. Qualitative interviews with tourists who have swum with captive dolphins identified their immediate recollections and stressed the grace, size and power of dolphins, but also a belief that the experience was too staged, too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…These feelings are explicitly represented in many of the in vivo responses gathered in this research thereby giving further credence to the few studies that assert that 'peak aesthetic experiences' are often 'achieved through the nature experience' (Chenoweth & Gobster, 1990;Mannell, 1996, p. 407) and more specifically with human -animal encounters (Curtin, 2006;Curtin & Wilkes, 2007;DeMares & Krycka, 1998;Laski, 1968;Wilson, 1984). Peak experiences can be linked to cathartic experiences that can make the participants' everyday problems temporarily diminish.…”
Section: Wonderment and Awementioning
confidence: 85%
“…These feelings are explicitly represented in many of the in vivo responses gathered in this research thereby giving further credence to the few studies that assert that 'peak aesthetic experiences' are often 'achieved through the nature experience' (Chenoweth & Gobster, 1990;Mannell, 1996, p. 407) and more specifically with human -animal encounters (Curtin, 2006;Curtin & Wilkes, 2007;DeMares & Krycka, 1998;Laski, 1968;Wilson, 1984). Peak experiences can be linked to cathartic experiences that can make the participants' everyday problems temporarily diminish.…”
Section: Wonderment and Awementioning
confidence: 85%
“…The reason being that most links in networks that are inferred from time series arise, in fact, mainly due to indirect interactions between two nodes through intermediate nodes or from "common-driver" nodes. This issue has arisen, and was shown to be important in various different disciplines (see, e.g., [24][25][26][27][28][29][30]). Different approaches to tackle this problem include partial correlation, conditional mutual information, and conditional Granger causality [26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…However, not all zoos and aquariums are effective in these endeavors (Curtin and Wilkes, 2007;Marino et al, 2010). Jiang et al (2007) found that people who had visited a captive cetacean facility had significantly less conservation concern and knowledge than in the control group who had never visited a marine park.…”
Section: Meeting Our Responsibilitiesmentioning
confidence: 99%